The Effectiveness of Problem-Based Learning Based on the Learning Management System on Critical Thinking Skills of Electronics Course Students - Ramdhani, Mohamad; Aprillia, Bandiyah Sri; Kustiawan, Iwan (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2021)
This study aims to apply problem-based learning (PBL) by utilizing the Center for e-Learning and Open Education (CELOE) Learning Management System (LMS) and analyze the effectiveness of the implementation of PBL on the LMS CELOE media in improving students' critical thinking problem-solving skills in the Electronics course. The Classroom Action Research Method (CAR) applies the research model initiated by Kemmis and Mc Taggart. Based on the observation results, LMS-based Project Based Learning is able to improve students' critical thinking and problem-solving abilities in the Electronics course. This statement can be confirmed from the results of repeated observations, namely the first and second cycles provide an increase in the post-test scores compared to the pretest scores. The level of effectiveness of the PBL method for Electronics courses in LMS in an effort to improve critical thinking, reached a value of 78% or can be said to be effective. In addition, the existence of discussion forums makes students active in communicating during the problem-solving process.